• Advertisement
Sign in to follow this  

Problems with collision solver techniques, please help quickly!

This topic is 4827 days old which is more than the 365 day threshold we allow for new replies. Please post a new topic.

If you intended to correct an error in the post then please contact us.

Recommended Posts

I'm working on a collision simulation following Chris Hecker's papers and i'm using his formulas. Now i have this particular case: (node: coefficent of restitution e = 1.0) Two objects (m1, m2) collide, where m1 is moving with v1 nad m2 is stationary. Some time ago i've learned that in a 1D collision (which is the case here since both objects are resting on a frictionless plane) i can get the velocityes like so: v1' = (m1v1 + m2v2) / (m1 + m2) - v1 v2' = (m1v1 + m2v2) / (m1 + m2) - v2 (v1 and v2 as vectors). now in my case, for m2 the stationary object this would simplify to: v2' = m1v1 / (m1 + m2) since v2 = 0 Now following Chris Hecker's formulas, ignoring rotation: j = -(1 + e)(v1 - v2) / (1 / m1 + 1 / m2) which turns into: j = -2 v1 ( (m1 + m2) / m1m2 ) j = -2 v1 m1 m2 / (m1 + m2) for object 2: v2' = v2 - j / m2 v2 = 2 v1 m1 m2 / (m1 + m2) * (1 / m2) = -2 v1 m1 (m1 + m2) now how come i get v2' = m1 / (m1 + m2) v1 from the first formulas and v2' = 2 m1 / (m1 + m2) v1 from the second formulas why double?? i'm really confused about this as i have done a laboratory experiment of this and the results stick to the first formula. I've derived Heckers formula myself and it turns out the same, and in other cases it appears to work nicely, what is happening here? [Edited by - Ilici on December 5, 2004 5:01:35 AM]

Share this post


Link to post
Share on other sites
Advertisement
v2' = 2 m1 / (m1 + m2) v1 from the second formulas

this looks correct. if m1 = m2,

V2' = 2 * (0.5f) * v1 = v1

so ball2 will have velocity V1, ball 1 will have velocity 0. The velocity transfers from one to the other, like in pool.

in this, they have

v1' = [(m1 - m2) v1 + 2.m2 v2] / [m1 + m2]
v2' = [2.m1 v1 + (m2 - m1) v2] / [m1 + m2]

I think your first two equations are wrong.

(googled on : "v1' = (m1v1 + m2v2) / (m1 + m2) - v1" and strangely enough, brought a lot of results [smile]. google rocks!).

Share this post


Link to post
Share on other sites
Ok, thanks a lot, i found it out myself short time ago when making the first mass much bigger i got weird results. Thanks anyway though!

Share this post


Link to post
Share on other sites
Sign in to follow this  

  • Advertisement